THE MORAL VALUES IN SPORT - Bekbergenov Toktarbay Dilimbetovich; Ismaylov Bayrambay Djabbarbergenovich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article is devoted to the study of morality in sport has attracted the interest of many sport psychologists, partly because of the pervasive and long-held belief across many scholars and lay people that sport builds character. Research in this area of sport psychology (SP) has looked at whether sport participation is indeed linked to moral behavior by examining issues pertaining to moral development, moral reasoning, and an array of prosocial and antisocial behaviors. This article presents work on values in sport, pioneered by Martin Lee, which was based on research in social psychology conducted first by Milton Rokeach, and subsequently by Shalom H. Schwartz.